Evaluation of official Medicolegal Documents About Police Custodies in Turkey Before Istanbul Protocol Trainings - Ünüvar, Ümit; Can, Özgür; Fincancı, Şebnem Korur; Bakkalcı, Metin; Tellioğlu, Ahmet; Özdemir, Bahattin; Özdemir, Çağlar; Kırteke, Elif; Kapkın, Emre; Güven, Ertan; Ulaş, Halis; Üçpınar, Hülya; et al. (The Bulletin of Legal Medicine, 2014)
Official medico-legal documents about police custodies in Turkey were reviewed in the framework of the project named “Istanbul Protocol Training Programme: Enhancing the Knowledge Level of Non- Forensic Expert Physicians, Judges and Prosecutors” conducted by Turkish Medical Association and International Rehabilitation Council for Torture Victims, in 2007-2009.The objectives of this study were to assess a process of medico-legal examinations and the quality of documents for detainees, before the Istanbul Protocol trainings and to determine whether the whole process followed was suitable in terms of Istanbul Protocol and to developed appropriate recommendations. Documents prepared just before the trainings by state employed physicians describing medical examination before and after police custodies were reviewed in Turkey.A multi-centered qualitative study was planned to reflect the overall country. One medico-legal document prepared before-police-custody and another document prepared after-police-custody on 61 different days between January 2008 and February 2009 were requested from 42 different units in 14 cities. A total of 1288 medico-legal documents were evaluated by using the General Medico-Legal Examination Report Form's questions involving the principles of forensic medicine services issued in a circular letter by the Ministry of Health in 2005.The analysis showed no differences between all cities and all units in terms of suitability of Istanbul Protocol. Of 1288 documents 86% had no formal structure such as including forensic medicine specialists need training for Istanbul Protocol.Key Words: Forensic medicine, Training, Standard examination forms, Medico-legal documentation, Istanbul Protocol.
Keywords: forensic medicine; training; standard examination forms; medico-legal documentation; istanbul protocol